Modulation of murine lymphocyte responsiveness by the saliva of Rhodnius prolixus (Hemiptera: Reduviidae) - Kalvachová, P; Hríbalová, V; Kodym, P; Volf, P (Journal of medical entomology, 1999)
Incorporation of 3H-thymidine by splenic lymphocytes was studied in CBA mice that were bitten by the triatomine bug Rhodnius prolixus (Stål) 14, 7, 4, and 2 d before lymphocyte isolation, respectively. In bitten mice, both spontaneous and mitogen-induced proliferative responses were reduced. The most pronounced effect was observed 4 d after exposure when lymphocytes were significantly suppressed in proliferative response to the mitogens concanavalin A, phytohemagglutinin, and bacterial lipopolysaccharide. The maximum inhibition caused an 85% reduction of proliferation and was observed in phytohemagglutinin-stimulated cell cultures. The immunosuppressive effect was caused neither by stress nor by an nonspecific cytotoxic effect of R. prolixus saliva. The described immunosuppressive activity of saliva could aid in successful repeated feedings of R. prolixus on the same host and possibly could play a role in transmission of Trypanosoma cruzi.
Keywords: sliny; Saliva; Mice; kousnutí a bodnutí hmyzem; Female; Rhodnius; Mice, Inbred CBA; Animals; myši inbrední CBA; ženské pohlaví; Insect Bites and Stings; Lymphocytes; lymfocyty; myši; zvířata